COMMUNITY EMPOWERMENT STRATEGY AROUND FORESTS THROUGH COMMUNITY FOREST MANAGEMENT SYSTEM (PHBM) IN PRINGAPUS DISTRICT SEMARANG DISTRICT - Meswari Dwi Hadiyanto; Sriroso Satmoko; Mukson Mukson (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
Forest Management in Java is carried out by Perum Perhutani, which has implemented a Community-Based Forest Management (PHBM) system. Pringapus Kecanatan has a State Forest which is quite extensive, however, most of the population around the forest is still in poor condition. The condition of the community around the forest in Pringapus District is illustrated by the people who do not have independence, do not have access to use the forest, the level of education and skills are still low. In an effort to overcome all this, Perum Perhutani is empowering the community in Pringapus District through the Community Forest Management System. This system is considered quite strategic because it is very accommodating to the interests of various parties including the community as the agents of development. This study aims to evaluate the implementation of the Collaborative Forest Management System (PHBM) from the Institutional aspect, the Empowerment aspect, the Agribusiness aspect and the LMDH Role aspect and formulating a community empowerment strategy through the PHBM. Analysis of the data used to answer the objectives is descriptive analysis, multiple linear regression analysis and SWOT analysis. The results of PHBM research in Pringapus sub-district indicate that the institution is being illustrated by the lack of realization of work programs as well as sub-optimal level of LMDH participation